Malalignment of anterior teeth in relation to orthodontic treatment experience and satisfaction with dental appearance in a group of adolecens in Norway - Punsvik, Lotte; Eriksen, Astrid Amalie (Universitetet i Tromsø, 2010)
The purpose of this study was to compare the relationship between some of the most common traits of malocclusion in Norway, overjet and anterior displacement, to satisfaction with dental appearance and treatment experience. Prevalence of malocclusions was studied in a sample of 55 adolescents, aged 14-15 years, from the city of Fauske in Northern Norway. Overjet and displacement were recorded on dental casts, and satisfaction with dental appearance was evaluated from a questionnaire. Subjects with lower anterior displacement of 4 mm or more were significantly more dissatisfied with their dental appearance as compared to subjects who had mandibular dental displacement less than 4 mm. No significant association was found between displacement in the maxilla and satisfaction. Almost all subjects (94,5%) with displacement of 4 mm or more in the maxilla had not received orthodontic treatment, and the orthodontically treated adolescents showed significantly less often anterior dental displacement in the maxilla compared to the non-treated subjects. In general, severe malocclusions were rare among our subjects, but moderate displacement of anterior teeth seems to be more common among non-treated than in treated individuals. It seems that mandibular anterior dental displacement may negatively affect one’s satisfaction with the dental appearance.